Odpowiedzi

2010-02-20T17:44:42+01:00
10x+5x-3x= 12x
12x+10x-4x=18x
7x²-3x²+x²= 5x²
4x+8x-5x= 7x
3x+4x-9x= -2x
8x²y+6y²-17x²y= -9x²y +6y²
-x-3x+2x= -2x
y²-6y²+10y²= 5y²
12x-10x-4x= -2x
-2x-7x+16x= 7x
Najlepsza Odpowiedź!
2010-02-20T17:47:27+01:00
-10x+5x-3x= -8x
12x+10x-4x=18x
7x²-3x²+x²=5x²
4x+8x-5x=7x
3x+4x-9x=-2x
8x²y+6y²-17x²y=---
-x-3x+2x=-2x
y²-6y²+10y²=5y²
12x-10x-4x=-2x
-2x-7x+16x=7x
  • Mint
  • Początkujący
2010-02-20T17:47:31+01:00
= -8x
=10x
=5x (kwadrat)
=7x
= -2x
=
=5x
=4y(kwadrat)
= -2x
=7x